Experimental investigation on the engine performance and emission behaviour of turpentine - diesel dual fuel operated modified DI diesel engine / R. Karthikeyan … [et al.] - Karthikeyan, R.; Nallusamy, N.; Alagumoorthi, N.; Ilangovan, V. (UiTM Press, 2011)
The dual fuel technique offers the advantage of easy conversion of the diesel engine to work on the dual fuel mode with little engine modifications. In this mode, the primary fuel (turpentine) is inducted along with inlet air stream and the pilot fuel (diesel) is injected through the regular injection system. The primary fuel (turpentine) shared the maximum energy in the power production but the pilot fuel shared only a least part and act as an ignition source. The engine with this facility has been operated under various load conditions and at various turpentine energy shares. The energy share that provides better performance has been identified and compared with diesel fuel operation. From the obtained results it was proved that this engine offered higher BTE at full load and smoke free operation at all loads. The CO and HC emissions were higher and operated with very low NOx emission at all loads. The results also proved that the dual fuel operation successfully replaced 75% of diesel usage with turpentine fuel.